Service Mashups Using Natural Language and Context Awareness: A Pragmatic Architectural Design - Belaunde, M.; Hassen, S. B. (2011 IEEE 15th International Enterprise Distributed Object Computing Conference Workshops, 2011)
In order to facilitate the combination of various facilities available from the internet as well as communication facilities offered by telecom operators, significant work is done to help end-users to create their own service mashups. In this paper we present our approach to build a composition tool capable of building on-the-fly service orchestration directly from the interpretation of requests expressed using a restricted form of natural language.